Technology Entrepreneurship Project (ENT 600) : Adidas / Khairun Hanna Mohd Afendy - Mohd Afendy, Khairun Hanna (2021)
When it comes to physical activities, the first important thing is the safety of the person performing the activities. One of the safety measures should be taken is the needs of proper shoes. There are varieties of sport shoes that are sell in various store. One of the shoes that attract me to carry out a case study is the Adidas Core Grace Women. These colourful training shoes may enhance the attraction of customer with its advantages and the beautiful design is a must buy item. Even though, the shoes may have its many benefits, but unfortunately it had the disadvantages as well. The disadvantages had cause severe disappointment among customers. Other than that, Adidas Core Grace shoes produces smelly odour due to the excessive sweat of the wearer. Due to lack of airflow in and out of the shoes, the smell had remained sustained. To recapitulate, the need to produce better version of the shoes is acquired so that it can overcome the problem as stated above and manage to satisfy the needs and wants of the customers.